Impact on the scape of Farfugium japonicum var. japonicum (Asteraceae) under strong wind conditions based on morphological and mechanical analyses - Shiba, Masayuki; Arihara, Shuma; Harada, Shiori; Fukuda, Tatsuya (Frontiers in Plant Science, 2024)
Adaptation of Farfugium japonicum (L.) Kitam. var. japonicum (Asteraceae) to the strong wind environment of coastal areas has been shown to reduce lamina size and shorten petioles; however, their effects on other traits of this species remain unknown. Our morphological analyses showed that shortening of the scape of this species is correlated with shortening of the petiole in coastal areas. The results suggested that when the height of the scapes became higher than that of the petioles, the wind stress on the scapes became stronger and their growth was suppressed. Therefore, the populations in coastal areas with strong winds had significantly shorter scapes than inland populations, and the height of petioles and scapes in the coastal populations were correlated. Further mechanical analysis by three-point bending tests revealed that the scapes had higher strength than the petioles. This species is evergreen and can produce new leaves regardless of the season, even if it loses its leaves by strong winds; however, because scapes only develop above ground for a limited period of the year, the loss of the scapes by strong winds has a significant impact on reproduction in that year. Therefore, even though the scapes were stronger than the petiole, shortening the scapes plays an important role in reducing strong wind stress in coastal areas.